2011
DOI: 10.1111/j.1365-2966.2011.20076.x
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological profiles and optical turbulence in the free atmosphere with NCEP/NCAR data at Oukaïmeden - I. Meteorological parameters analysis and tropospheric wind regimes

Abstract: In this paper, we have used the National Centers for Environmental Prediction (NCEP)/National Centers for Atmospheric Research (NCAR) Reanalysis data base to study, first, a comparison between balloon sounding made at different stations with coinciding model‐based meteorological analysis. The comparison allows the assessment of reliability of the analysis in the studied period and to highlight NCEP/NCAR Reanalysis as an interesting data base for site characterization. Using the same system of Reanalysis, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 40 publications
1
20
1
4
Order By: Relevance
“…One the most important astroclimatic characteristics analyzed in many astronomical observatories of the world and describing the rate of turbulence change in the optically active atmospheric layer is the wind velocity in the upper troposphere in the jet stream zone [Bounhir et al, 2009;Chueca et al, 2004;García-Lorenzo et al, 2009;Hash et al, 2011]. It has been shown that for SSO and BAO an indicator of optical turbulence changes may be the wind velocity at a pressure level of 200 hPa V 200 at a height of ~12 km [Bolbasova et al, 2019].…”
Section: Estimated Rate Of Wavefront Evolution and Distribution Of Homentioning
confidence: 99%
“…One the most important astroclimatic characteristics analyzed in many astronomical observatories of the world and describing the rate of turbulence change in the optically active atmospheric layer is the wind velocity in the upper troposphere in the jet stream zone [Bounhir et al, 2009;Chueca et al, 2004;García-Lorenzo et al, 2009;Hash et al, 2011]. It has been shown that for SSO and BAO an indicator of optical turbulence changes may be the wind velocity at a pressure level of 200 hPa V 200 at a height of ~12 km [Bolbasova et al, 2019].…”
Section: Estimated Rate Of Wavefront Evolution and Distribution Of Homentioning
confidence: 99%
“…Одной из важнейших астроклиматических характеристик, анализируемой во многих астрономических обсерваториях мира и описывающей скорость изменения турбулентности в оптически активном слое атмосферы, является скорость воздушного потока в верхней тропосфере в зоне струйного течения [Bounhir et al, 2009;Chueca et al, 2004;García-Lorenzo et al, 2009;Hash et al, 2011]…”
Section: оценка скорости эволюции волнового фронта и распределение гоunclassified
“…С учетом среднего разброса коэффициента пропорциональности k ожидаемое значение турбулентной скорости V 0 составит от 7.9 до 11.8 м/с. Полученные характерные значения V 0 согласуются с расчетами этой величины для астрономической обсерватории Тейде [García-Lorenzo et al, 2009], для которой V 0 может достигать ~18 м/c, а ее характерные значения изменяются от 3.8 до 8.2 м/c. Проанализирована метеорологическая обстановка и получен вертикальный профиль структурной характеристики флуктуаций показателя преломления воздуха для условий слабой интегральной турбулентности по лучу зрения в ССО.…”
Section: обсуждение полученных результатовunclassified
See 1 more Smart Citation
“…Results are compared to those obtained from correlations of slopes only or of scintillation only. Then, the CO-SLIDAR profiles are compared to profiles estimated from meteorological data, from NCEP (National Centers for Environmental Prediction)/NCAR (National Centers for Atmospheric Research) Reanalysis data base [14]. We finally discuss CO-SLIDAR's contribution as a new C 2 n profiler and we suggest some improvements.…”
Section: Introductionmentioning
confidence: 99%